Characteristics of patients and physicians correlated with regular influenza vaccination in patients treated for type 2 diabetes: a follow-up study from 2008 to 2011 in southeastern France. (October 2015) - Verger, P.; Cortaredona, S.; Pulcini, C.; Casanova, L.; Peretti-Watel, P.; Launay, O.
Abstract: We studied a cohort of 110 823 patients treated with oral hypoglycaemic agents for type 2 diabetes in southeastern France from 1 January 2008 to 31 December 2011, to identify influenza vaccination coverage trends and the patient and physician correlates of influenza vaccine (IFV) uptake. We used French national health insurance fund (NHIF) databases to identify these patients and collect data on their IFV reimbursement claims (IFVC) and patient and physician characteristics. We used multilevel multivariate polytomous logistic regressions to test the correlates of IFVC. Between 2008 and 2011 the annual IFVC rate varied from 33.7% to 32.3% in the 18–64 age group and from 69.5% to 61.1% in the 65 + age group, among whom we saw a clear trend towards reduced vaccination after 2008. In the younger group, the probability of regular vaccination each year from 2008 to 2011 increased with diabetes severity and duration, comorbidities, and the number of general practitioner and nurse visits; it was higher among patients seeing endocrinologists and lower among low-income patients than in other patients. In the older group, there was no association with either diabetes severity or physician specialty. These results suggest different patterns of correlates of influenza vaccination according to age. Endocrinologists might help to improve IFV uptake in the younger group of patients with type 2 diabetes. Communication strategies regarding influenza vaccination should be adapted to age, and collaboration between healthcare professionals should be reinforced to achieve vaccination objectives for these patients.